Factors related to health civic engagement: results from the 2018 National Survey of Health Attitudes to understand progress towards a Culture of Health - Tamara Dubowitz; Christopher Nelson; Sarah Weilant; Jennifer Sloan; Andy Bogart; Carolyn Miller; Anita Chandra (BMC, 2020)
Abstract Background Civic engagement, including voting, volunteering, and participating in civic organizations, is associated with better psychological, physical and behavioral health and well-being. In addition, civic engagement is increasingly viewed (e.g., in Robert Wood Johnson Foundation's Culture of Health action framework) as a potentially important driver for raising awareness of and addressing unhealthy conditions in communities. As such, it is important to understand the factors that may promote civic engagement, with a particular focus on the less-understood, health civic engagement, or civic engagement in health-related and health-specific activities. Using data from a nationally representative sample of adults in the United States (U.S.), we examined whether the extent to which individuals feel they belong in their community (i.e., perceived sense of community) and the value they placed on investing in community health were associated with individuals' health civic engagement. Methods Using data collected on 7187 nationally representative respondents from the 2018 National Survey of Health Attitudes, we examined associations between sense of community, valued investment in community health, and perceived barriers to taking action to invest in community health, with health civic engagement. We constructed continuous scales for each of these constructs and employed multiple linear regressions adjusting for multiple covariates including U.S. region and city size of residence, educational attainment, family income, race/ethnicity, household size, employment status, and years living in the community. Results Participants who endorsed (i.e., responded with mostly or completely) all 16 sense of community scale items endorsed an average of 22.8% (95%CI: 19.8-25.7%) more of the health civic engagement scale items compared with respondents who did not endorse any of the sense of community items. Those who endorsed (responded that it was an important or top priority) all items capturing valued investment in community health endorsed 14.0% (95%CI: 11.2-16.8%) more of the health civic engagement items than those who did not endorse any valued investment in community health items. Conclusions Health civic engagement, including voting and volunteering to ultimately guide government decisions about health issues, may help improve conditions that influence health and well-being for all. Focusing on individuals' sense of community and highlighting investments in community health may concurrently be associated with increased health civic engagement and improved community and population health.